Recombination of charge carriers in heterostructures with Ge nanoislands grown on Si(100) - Kondratenko, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
In this paper, the study of the recombination of non-equilibrium charge carriers and determination of recombination mechanisms in Ge/Si heterostructures with nanoislands have been presented. The effects of long-term photoconductivity decay in Ge/Si heterostructures with Ge nanoislands have been found as caused by variations of the electrostatic potential in the near-surface region of Si(100) substrate and spatial separation of electron-hole pairs between localized states of Ge nanoislands and states of wetting layer and Si. It has been shown that the photoconductivity decay depends on the excitation energy and temperature, while Ge nanoislands are Shockley-Read recombination centers with a higher recombination rate as compared with Si.